Estimasi cadangankarbon Estimasi Cadangan Karbon Kwasan Bale Mangrove Sebagai Upaya Mitigasi Perubahan Iklim di Wilayah Pesissir Desa Jerowaru: estimasi cadangan karbon kawasan bale mangrove sebagai upaya mitigasi perubahan iklim - febi utari, yenni; agus, putra muliadi; rahayu, dwi (Jurnal Teknologi Lingkungan, 2025)
Global climate change is an instability of the earth's atmosphere that causes anomalies in numbers, air parameters, and temperature. Climate change is theaverage change in one element in a particular area. Increasingly significant global temperatures like this will have a very serious impact on the human environment. The main cause of climate change is largely due to human activities The purpose of this study was to determine the estimated carbon stocks of the mangrove bale area as an effort to mitigate climate change in Jerowaru Village. The method used was a quantitative descriptive method through measuring the stem diameter (DBH) with an allometric model approach to calculate above and belowground biomass, and then converted into carbon stocks. There were 4 (four) mangrove species found at the research location, namely Rhizopora apiculate, Rhizopora mucronata, Rhizopora stylosa, Sonneratia alba. The results of the biomass and carbon storage calculations where the species in the Jerowaru Village Mangrove Forest Area The most dominant species found were Rhizopora apicculata and Sonneratia alba. The total biomass of 7672.1 ton/ha trees has a carbon storage value of 191.8 ton/ha, with a total AGB of 28051071.15 ton/ha. The total biomass of 302,166 saplings has a carbon storage value of 7.55 ton/ha, with a total AGB of 1711440.11 ton/ha.